Characterization of a self-sufficient trans-anethole oxygenase from Pseudomonas putida JYR-1. - Dongfei Han; Michael J Sadowsky; Youhoon Chong; Hor-Gil Hur (PLoS ONE, 2013)
A novel flavoprotein monooxygenase, trans-anethole oxygenase (TAO), from Pseudomonas putida JYR-1, which is capable of catalyzing the oxidation of trans-anethole to p-anisaldehyde, was heterologously expressed in E. coli and purified. Enzymatic kinetics of diverse substrates and cofactors revealed that TAO is likely to be a novel self-sufficient flavoprotein monooxygenase. Enzyme assays of GST-TAO demonstrated that TAO catalyzed a trans-anethole oxidation reaction without auxiliary component enzyme-like electron-transfer flavin reductases. The single component TAO had the ability to reduce flavin cofactors and simultaneously oxidize trans-anthole to p-anisaldehyde. In the processes of reduction of flavin and oxidation of trans-anethole, TAO accepted various flavin and NAD(P)H cofactors. TAO also catalyzed oxidation of isoeugenol, O-methyl isoeugenol, and isosafrole, all of which contain the 2-propenyl functional group on the aromatic ring structure with different catalytic efficiency. TAO had the greatest catalytic efficiency (k cat/K m) with the original substrate, trans-anethole. Investigation about partially deleted mutants of TAO indicated that reductase active sites appeared to be located near the N terminal. Site directed mutagenesis studies also proved that the proposed flavin binding sites, Trp-38, Thr-43, Tyr-55, were critical for flavin reduction. However, disruption of any portion of TAO eliminated the oxygenase activity.